What drives the vital rates of secondary hemiepiphytes? A first assessment for three species of Heteropsis (Araceae) in the Colombian Amazon. (17th April 2015) - Balcázar-Vargas, María Paula; van Andel, Tinde R.; Westers, Paul; Zuidema, Pieter A.
Abstract: Secondary hemiepiphytes rely on other plants (hosts) to grow vertically. After germinating on the forest floor, their seedlings search a host to ascend. We recorded information on survival, growth, reproduction and vegetative propagation of three Heteropsis species, to evaluate what drives their vital rates. We measured 700 individuals of each study species between 2007 and 2009 in the southern Colombian Amazon. A gradual increase in stem length, leaf size, number of roots and plagiotropic branches was found with increasing height of Heteropsis individuals on their hosts. Survival of leafless non-climbing seedlings was very low (28% annually); increasing substantially (84–94%) once the seedling had ascended a host. The three Heteropsis species presented slow height growth rates ( c . 2–8 cm y −1 ) with large variation, while a substantial percentage of the stems (31–62%) did not grow or dried out. Vegetative propagation in Heteropsis may act as a dispersion-propagation strategy to find a suitable host and reach the canopy again after falling. The slow growth rates suggest that Heteropsis individuals that have reached the canopy are rather old. Once plants have reached the tree crowns, their longevity is largely determined by the survival of the host tree.